Enhancing spectral response towards high-performance dye-sensitised solar cells by multiple dye approach: A comprehensive review. (December 2021) - Akhtaruzzaman, Md.; Shahiduzzaman, Md.; Selvanathan, Vidhya; Sopian, Kamaruzzaman; Hossain, Mohammad Ismail; Amin, Nowshad; Hasan, A.K. Mahmud
Highlights: ● Each dye can only absorb a specific part sunlight absorption spectrum. ● Co-sensitization of metal and metal free organic dyes are the center of this study. ● Higher power conversion efficiency (PCE) can be achieved by co-sensitization method. ● Optimized device gives better PCE than that of individual sensitizer. ● This holistic study could help for progress in dye-sensitized solar cell in future. Abstract: Dye-sensitized solar cells (DSSCs) are potential candidates for the latest solar cell technologies because of their advantages: low manufacturing cost, flexibility, light weight, easy processing, color variety, and translucent features. However, an important DSSC component, the sensitizer, still has an inefficient sunlight absorption profile, reducing cell efficiency. Several studies have been conducted on co-sensitization in the last decade to improve panchromaticity light absorption and increase DSSC performance by mixing dyes, absorbing different regions of the solar magnetic radiation spectrum, which allows designing, synthesize, and analyze various types of sensitizers and co-adsorbents. The dye samples of co-sensitization described thus far have focused on the selection of appropriate co-sensitizers for use in combination with well-known high-performing dyes, such as Zn-porphyrins to organic, Ru-based organic complexes to organic and organic to organic sensitizers. The co-dye DSSC device with Ru-organic dye (N719+7-BC), organic-organic dye (BD+ U -01), and Zn-porphyrin-organic dye (SGT-149+SGT-021) as absorber exhibited the highest power conversion efficiency (PCE) of 9.68%, 10.56%, and 14.26%, respectively superseding the PCE of each of the individual dyes. This study provides a detailed review of panchromaticity in DSSCs, covering the previous and most recent development in this field which will further contribute to the advancement of this area. Graphical abstract: Image, graphical abstract